2016
DOI: 10.1039/c6pp00171h
|View full text |Cite
|
Sign up to set email alerts
|

The excitation intensity dependence of singlet fission dynamics of a rubrene microcrystal studied by femtosecond transient microspectroscopy

Abstract: When a rubrene crystal was excited with an intense fs pulse (397 nm), transient local heating (∼ps) of the crystal through nonradiative relaxation from SN to S1 accelerates singlet fission of the S1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 34 publications
(76 reference statements)
3
32
0
Order By: Relevance
“…28 Previous studies of rubrene-DBP TTA-UC systems include in some form the assertion that FRET from rubrene to DBP outcompetes singlet fission. 18,[26][27][28] This simple statement appears to overlook the complexity of singlet fission and triplet fusion that occurs in solid rubrene, dynamics that have been extensively studied in vapour-grown orthorhombic single crystals [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] and to a lesser degree in more complex thin films. 25,30,[46][47][48][49][50][51] Furthermore, transient absorption spectroscopy of rubrene single crystals has shown that S 1 -1 (TT) occurs extremely rapidly, with reported time constants varying from 25 fs 35,36 to 2 ps.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Previous studies of rubrene-DBP TTA-UC systems include in some form the assertion that FRET from rubrene to DBP outcompetes singlet fission. 18,[26][27][28] This simple statement appears to overlook the complexity of singlet fission and triplet fusion that occurs in solid rubrene, dynamics that have been extensively studied in vapour-grown orthorhombic single crystals [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] and to a lesser degree in more complex thin films. 25,30,[46][47][48][49][50][51] Furthermore, transient absorption spectroscopy of rubrene single crystals has shown that S 1 -1 (TT) occurs extremely rapidly, with reported time constants varying from 25 fs 35,36 to 2 ps.…”
Section: Introductionmentioning
confidence: 99%
“…25,30,[46][47][48][49][50][51] Furthermore, transient absorption spectroscopy of rubrene single crystals has shown that S 1 -1 (TT) occurs extremely rapidly, with reported time constants varying from 25 fs 35,36 to 2 ps. 33,34 FRET from rubrene to DBP is therefore very unlikely to outcompete this first singlet fission step for the majority of excitons. In ESI, ‡ Section S11, we estimate the rubrene-DBP FRET rate to be 1.5 ps for nearest neighbours based on previous calculations of the Fo ¨rster radius.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Femtosecond transient absorption experiments on crystalline RUB suggested that the majority of SF occurs within 1 ps 27 , but later experiments indicated that this rate may depend on excitation density and thermal load. 23 Our excitation densities are below those typically used in transient absorption experiments, and our SF time of 60 ps approaches the 35 ps time seen at the lowest fluences in such experiments. 23 But the distorted PL spectrum makes it impossible to unequivocally identify the emitting species as the high energy species, so it is also possible that we are measuring the dynamics of a subset of sites within the crystal rather than the majority species seen in the transient absorption experiments.…”
Section: Resultsmentioning
confidence: 45%
“…Our samples were powdered in order to pack the melting point capillary, and this process leads to an unstructured emission peaked at around 600 nm, shown in Figure 1, the same wavelength observed for most single crystals. 21,23 This redshifted emission probably reflects strong selfabsorption in the sample 19 , but may also include contributions from defect states created by powdering. After the crystal melts, this emission shifts slightly to higher energy and broadens, but does not undergo dramatic changes in shape or intensity.…”
Section: Resultsmentioning
confidence: 99%